Exploring Female Sexuality in Zeenuth Futehally’s Zohra - Abbas, Aisha Mohammad Yamin Aroj (South Asian Journal of Social Sciences and Humanities, 2022)
The existentialist philosopher, Simone De Beauvoir, in her prominent book, The Second  Sex, states that “one is not born, but rather becomes a woman.” (Beauvoir, 2011). This  statement is built upon the idea that woman; or rather sexuality/gender performance is a  social product resulting from society and physiological training. The term ‘woman’ is the  aforementioned phrase alludes to the romanticized version of woman as perceived by the  society. So, rather than being inherent, womanhood is something that a woman strives to  achieve in order to become ideal. In the light of such statement, this paper aims to dismantle  the notion that sexuality is a natural phenomenon by exploring Zeenuth Futehally’s Zohra, a  novel set during the pre-partition period, and involving characters from aristocracy class, and  also to represent how gender ideology prevalent in West affected the gender ideology in  India.
Keywords: Muslim Women; Sexuality; Gender; History; Feminism; Elite Class